EFFECTS OF BIOCHAR FROM OIL PALM BIOMASS ON SOIL PROPERTIES AND GROWTH PERFORMANCE OF OIL PALM SEEDLINGS - NIN HWONG, CHIA; FONG SIM, SIONG; KHOON KHO, LIP; ARN TEH, YIT; LUKE DAVID, HARROLD; HONG CHUA, KIAN; NAHRUL HAYAWIN, ZAINAL (Penerbit UMT, 2022)
Fertilizer is the most expensive input in oil palm cultivation. Biochar can be used to improve the nutrient use efficiency, reducing the cost of fertilizer. Application of biochar from oil palm biomass onto oil palms has been scarcely studied. This paper reports the effects of empty fruit bunch (EFB) and palm kernel shell (PKS) biochar on the soil properties and growth performance of oil palm seedlings. The EFB and PKS biochar used were slightly acidic to neutral (pH 6.08 – 7.10) with the former exhibiting well-defined macropores. The seedlings ameliorated with EFB biochar demonstrated improved plant height and biomass with increasing biochar dosage. Marked improvements in uptake of phosphorus, magnesium, calcium and boron were also observed in the palm seedlings treated with EFB biochar. This was associated with the enhanced soil cation exchange capacity (CEC) upon biochar treatment. These positive effects of EFB biochar on plants and soil however were not recorded in the treatment with PKS biochar as the biochar was characterized with marginal porous structures and poor CEC properties. The study concluded that the stimulatory effects of EFB biochar on soil properties and plant growth were primarily governed by the biochar morphology and its cation exchange properties.